Mechanical properties and reaction mechanism of microwave-activated crumb rubber-modified asphalt before and after thermal aging. (18th January 2021) - Yin, Lei; Yang, Xiaolong; Shen, Aiqin; Wu, Hansong; Lyu, Zhenfeng; Li, Bo
Highlights: The effect of thermal aging on the mechanical properties of ACRMA was evaluated. The reaction mechanism of ACRMA before and after aging was investigated. Microwave activation of crumb rubber improved the anti-aging properties of asphalt. Abstract: The anti-aging properties and related mechanism of microwave-activated crumb rubber-modified asphalt (ACRMA) were evaluated in this study. Physical and rheological tests were conducted on ACRMA before and after simulated thermal aging, and several microcosmic tests were performed to analyze the aging mechanism. The stiffness, plasticity, and viscoelasticity of ACRMA were less affected by aging than crumb rubber-modified asphalt (CRMA). After aging, ACRMA exhibited better high-temperature performance and permanent deformation resistance than CRMA. The thermal aging process of ACRMA was analyzed, and the anti-aging mechanism model was established. The anti-aging performance of ACRMA was better than that of CRMA.